Neoadjuvant docetaxel/estramustine prior to radical prostatectomy or external beam radiotherapy in high risk localized prostate cancer: A phase II trial - Kim, William Y.; Whang, Young E.; Pruthi, Raj S.; Baggstrom, Maria Q.; Rathmell, W. Kimryn; Rosenman, Julian G.; Wallen, Eric M.; Goyal, Lav K.; Grigson, Gayle; Watkins, Catharine; Godley, Paul A. (Urologic oncology, 2011)
Patients with locally advanced or organ confined, high risk, prostate cancer are at significant risk of having disease recurrence despite definitive local therapy. We evaluated the 2-year progression-free survival of subjects treated with chemotherapy administered prior to definitive therapy with surgery or radiation. Patients ( n = 24) with locally advanced and high risk localized prostate cancer were treated with neoadjuvant docetaxel 36 mg/m2 i.v. weekly for 3 weeks and estramustine 140 mg orally 3 times daily for 3 consecutive days every 28 days prior to definitive treatment with prostatectomy or radiation. All evaluable patients, except 1, completed the proposed cycles of neoadjuvant chemotherapy with minimal dose reductions or delays. Of the 22 evaluable patients, 12 underwent radical prostatectomy and 10 underwent external beam radiation therapy. Twenty-one of 22 patients achieved a prostate-specific antigen (PSA) reduction > 25%. There were no pathologic complete responses. With a median follow-up of 24 months, the 2-year progression-free survival was 45%. Our findings support the safety, tolerability, and efficacy of neoadjuvant chemotherapy in patients with men with high risk, locally advanced prostate adenocarcinoma, although the relative contributions of androgen deprivation therapy and docetaxel cannot be determined. The effectiveness of neoadjuvant chemotherapy in preventing prostate cancer relapses should be studied in a randomized trial.